Challenges and innovations in diagnosing nonphysical child abuse in pediatric emergency departments - Chibuike Daniel Onyejesi; Jose Carlos Del Castillo Miranda; Sohaila Mohamed Abdelbar; Mayam Mohamed Aziz; Eslam Abady; Janna Ahmed Omran; Alishah Zehra; Mohammed Alsabri (Pediatric Emergency Medicine Journal)
Child abuse is a widespread global health crisis with longterm implications for children’s physical, psychological, and emotional well-being. Pediatric emergency departments (PEDs) are often the first point of contact for children experiencing abuse, presenting unique diagnostic challenges due to the diverse manifestations of maltreatment. In contrast to physical abuse that often leaves visible markers, nonphysical abuse (e.g., emotional neglect or psychological harm) frequently go undetected, exacerbating underreporting and delayed interventions. This article examines the prevalence, diagnostic challenges, and multidisciplinary strategies for addressing child maltreatment in PEDs. Cultural and systemic barriers, coupled with insufficient training and resource constraints, hinder the recognition of subtle signs of nonphysical abuse. Advances in diagnostic imaging, behavioral assessment tools, and laboratory investigations are discussed as critical components of comprehensive evaluations. Multidisciplinary teams play a pivotal role in addressing the complexity of abuse cases, combining medical, psychological, and legal expertise to provide holistic care while minimizing additional trauma. The integration of artificial intelligence into diagnostic workflows is explored as a transformative innovation, offering potential for early detection of abuse patterns and enhanced decision-making. However, the implementation of artificial intelligence requires careful consideration to ensure that it complements human expertise and aligns with ethical standards. There is a need for standardized protocols, targeted training programs, and supportive systems to empower healthcare professionals in recognizing and reporting all forms of child maltreatment. We propose more research to develop tools capable of detecting nonphysical abuse in PEDs. By combining technological advancements, multidisciplinary collaboration, and educational initiatives, PEDs can improve outcomes for vulnerable children and address the widespread issue of child maltreatment more effectively.